Dental students’ perceptions of undergraduate clinical training in oral and maxillofacial surgery in an integrated curriculum in Saudi Arabia - Al-Dajani, Mahmoud (J Educ Eval Health Prof, 2015)
PURPOSE: The aim was to understand dental students’ experiences with oral and maxillofacial surgery (OMS) teaching, their confidence levels in performing routine dento-alveolar operations, and the relationship between the students’ confidence level and the number of teeth extracted during the clinical practice. METHODS: The survey questionnaire was distributed to 32 students at Aljouf University College of Dentistry, Saudi Arabia during their fourth and fifth year in 2015. Respondents were asked to rate 19 items, which represent a student’s confidence in performing routine surgical interventions, using a four-point Likert scale (1=very little confidence, 4=very confident). A multivariate regression was computed between average confidence and the variables: weekly hours devoted to studying oral and maxillofacial surgery, college grade point average, and the total number of teeth extracted. RESULTS: The response rate was 100%. Students revealed the highest level of confidence in giving local anesthesia (96.9%), understanding extraction indications (93.8%), and performing simple extractions (90.6%). Less confidence was shown with handling difficult extractions (50.0%), extracting molars with separation (50.0%) or extracting third molars (56.3%). The average confidence in performing surgical procedures was 2.88 (SD=0.55), ranging from 1.79 to 3.89. A given student’s confidence increased with an increase in the total number of teeth extracted (P=0.003). CONCLUSION: It reveals a significant impact of undergraduate clinical training on students’ confidence in performing oral and maxillofacial surgery clinical procedures: The more clinical experience the students had, the more confidence they reported.